Tindak Tutur Representative Dalam Quotes Taylor Swift Pada Qutetab.Com - Maulida, Meira Nuha (PT. Alahyan Publisher Sukabumi, 2023)
This study aims to identify the types of speech acts that represent a language through the quotes uttered by Taylor Swift on quotetab.com. The research method used is descriptive qualitative, namely by explaining the meaning contained in the utterances in the quotes in detail. The data collection technique was carried out by classifying speech acts based on representative utterances. Through this research, 36 citations were obtained which represented different representative speech acts, and statements were the type of speech act that appeared the most in the data.